Una semántica formal para Apache Spark en lógica de reescritura (2018)
This document presents an executable semantics for Apache Spark in rewrite logic. Apache Spark is a work environment open source designed for data processing that provides an application programming interface for the manipulation of large volumes of data. The Apache Spark executable semantics it is made available through a formal specification in Maude, this specification being executable and with which it is possible to study the dynamic behavior of Apache Spark's job scheduler.